Flouting Maxims in Alita Battle Angel Movie - I Gusti Ayu Vina Widiadnya Putri; Ida Ayu Mela Tustiawati; Katarina Ade Kusuma, Katarina (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The aims of this study are to analyze the types of flouting maxim and the reason for flouting maxim found in the Alita Battle Angel movie. Flouting maxims is an important thing to consider in making communication more effective and making the sentences acceptable for the listener. This study focused on analyzing the types of flouting maxim and the reason why the characters flout the maxim by using the theory from Grice (1975) is used to classify the types of flouting maxims and the theory from Leech (1983) is used to find out the reason for flouting the maxims. This study used descriptive qualitative method in analyzing the data and this study used note-taking technique in collecting the data. The result of the study showed that the types of flouting maxims found in the movie are 20 data. The highest occurrence in the Alita Battle Angel movie is the flouting maxim of relevance which takes 10 data (50%). The finding shows that the highest occurrence of flouting maxim is the flouting maxim of relevance and the collaborative reasons become the most dominant reason for flouting maxim in this movie.